Auto-organização de aglomerados finitos de dipolos magnéticos carregados - Bezerra, Italo Pereira (2009)
It is studied at this thesis a two-dimensional cluster of magnetic particles, with surface charge, confined by a circular parabolic potential. The particles have the same magnitude of magnetic dipole moment and the same amount and sign of surface charge. The goal of the present study is the characterization of the ground state configurations and the normal mode spectra of the cluster. The numerical study of the system is based on the Monte Carlo simulation technique, using the Metropolis Algorithm. It was also used the called Newton Method technique to reach the ground state configurations . The present study is divided in two parts: i) In the first one, the dependence of the equilibrium configurations and the normal modes is analyzed considering the presence or not of a external magnetic field. The magnetic dipole moment is taken as constant. ii) In the second one, the surface charge and the magnetic dipole moment are taken as constant, and the ground state configurations and the normal modes are studied as function the the external magnetic field intensity. At this part, it is also calculated the magnetization of the system as function of the external magnetic field. It was observed a great number of different ground state configurations, like concentric rings, and chains. The vibrational normal mode frequencies spectra was obtained by using the harmonic approximation. Due to the non-spatial symmetry of the magnetic dipole interaction, the normal modes must show an extra rotational component. It can be noted that due to surface charge of the particles the frequencies spectra can present elevated variation on the intensity. It can also be noted that some properties of the first case system also occurs on the second case system, and these properties are independent of the applied magnetic field, and in the second case system it can be noted that there are less different ground state configurations as compared with the first one.